Fieldwork challenges in diaspora communities: Arabic speakers in Germany and Pennsylvania German speakers in Canada - Neuhausen, Miriam; Adnan, Muhadj (Linguistics in Amsterdam, 2024)
This paper explores the complexities of conducting fieldwork and processing the collected data in the following two diaspora communities: Arabic speakers in Germany and Pennsylvania German speakers in Canada. Pointing out differences and similarities in working with the two socially and linguistically heterogeneous groups, we highlight the need for culturally sensitive research methodologies that acknowledge and adapt to the respective sociocultural and linguistic settings. If we do not acquire and implement community-specific sociocultural knowledge before, during and after the data collection process, important findings may not come to the surface. Providing examples from our fieldwork, we show how the researcher’s identity and interaction dynamics with the respective community have an immediate impact on the data collection and analysis processes. We attempt to offer practical recommendations and encourage linguists and social scientists to conduct fieldwork in similarly complex contexts to advance sociolinguistic theory in multilingual minoritised communities.